Identifying critical factors towards building a viable sadaqa house model in Malaysia - Engku Ali, Engku Rabiah Adawiah; Kassim, Salina; Syed Jaafar Alhabshi, Syed Musa; Hassan, Rusni; Hasan, Aznan; Syed Azman, Syed Marwan Mujahid (2015)
While the Islamic banking and finance industry has grown rapidly since its inception in 1983, there remain gaps in terms of its reach and inclusiveness. The current model of Islamic banking tends to favour the more affluent segment of the society, to the exclusion of the poor, also known as the un-bankables. In view of this, there is an urgent need to develop an integrated model of Sadaqa House that can address this issue. This study intends to identify crucial factors towards developing a viable integrated model of Sadaqa House in Malaysia through a critical review of the literature. Four essential dimensions will be examined, namely: legal; Shari'ah; accounting; and financial aspects in order to arrive at a practical model of the Sadaqa House. The findings of this study are expected to provide vital inputs on the critical factors necessary to address the issues and challenges in materializing the idea of Sadaqa House in Malaysia.